2013
DOI: 10.1074/jbc.m112.370924
|View full text |Cite
|
Sign up to set email alerts
|

The Role of γ-Secretase Activating Protein (GSAP) and Imatinib in the Regulation of γ-Secretase Activity and Amyloid-β Generation

Abstract: Background: ␥-Secretase activating protein, GSAP, was identified as a novel regulator of ␥-secretase and amyloid-␤ production. Results: Reducing GSAP expression in cells decreased amyloid-␤ generation. However, overexpression of GSAP in cells and recombinant GSAP in vitro did not modulate amyloid-␤ generation. Conclusion:The relationship between GSAP and ␥-secretase is unclear. Significance: GSAP is not a validated therapeutic target for Alzheimer disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
56
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(57 citation statements)
references
References 29 publications
1
56
0
Order By: Relevance
“…Nonessential factors, such as CD147, TMP21, γ-secretase activating protein (GSAP), β-arrestin-1 β-arrestin-2, Erin-2, syntexin-1, voltage-dependent anion channel 1 (VDAC1), contactin-associated protein 1 (CNTNAP1), TPPP and NDUFS7 have been found to be associated with the γ-secretase complex and modulate γ-secretase activity and specificity; (26, 8894) however, the functional significance of some of these interactions has been contended. (95, 96) (97) Moreover, γ-secretase has been shown to interact with tetraspanin-enriched microdomains, or lipid rafts. (98) It has been suggested that different γ-secretase complexes can contribute to substrate specificity, (99, 100) which is exemplified by genetic knockout of Aph-1b in a mouse AD model that improved the disease-relevant phenotypic features without Notch-related side effects.…”
Section: γ-Secretase and Aβ Peptidesmentioning
confidence: 99%
“…Nonessential factors, such as CD147, TMP21, γ-secretase activating protein (GSAP), β-arrestin-1 β-arrestin-2, Erin-2, syntexin-1, voltage-dependent anion channel 1 (VDAC1), contactin-associated protein 1 (CNTNAP1), TPPP and NDUFS7 have been found to be associated with the γ-secretase complex and modulate γ-secretase activity and specificity; (26, 8894) however, the functional significance of some of these interactions has been contended. (95, 96) (97) Moreover, γ-secretase has been shown to interact with tetraspanin-enriched microdomains, or lipid rafts. (98) It has been suggested that different γ-secretase complexes can contribute to substrate specificity, (99, 100) which is exemplified by genetic knockout of Aph-1b in a mouse AD model that improved the disease-relevant phenotypic features without Notch-related side effects.…”
Section: γ-Secretase and Aβ Peptidesmentioning
confidence: 99%
“…GSAP is synthetized from a larger 98 kDa protein, previously termed pion homologue protein (PION), which is rapidly processed into the predominant 16 kDa active form [5], resulting in the modulation of γ-secretase-Aβ production by its interaction with presenilin 1 (PS1) and APP-CTF without affecting notch cleavage [5]. In vitro and in vivo studies have demonstrated that changes in GSAP levels regulate Aβ production [57]. Studies in transgenic mouse models of AD have shown that pharmacological (using the kinase inhibitor imatinib) or genetic reduction of GSAP leads to a decrease in Aβ production, plaque development and tau phosphorylation [57].…”
Section: Introductionmentioning
confidence: 99%
“…In vitro and in vivo studies have demonstrated that changes in GSAP levels regulate Aβ production [57]. Studies in transgenic mouse models of AD have shown that pharmacological (using the kinase inhibitor imatinib) or genetic reduction of GSAP leads to a decrease in Aβ production, plaque development and tau phosphorylation [57]. GSAP immunoreactivity has been associated with neuronal PS1 and Aβ immunopositive plaques in the frontal cortex and hippocampus in AD [8].…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, in AD brains GSAP immunoreactive deposits are closely associated with Aβ-containing amyloid plaques (15). While conflicting reports on the influence that peripheral GSAP pharmacological blockade may have on Aβ levels (16,17), we recently showed that intra-cerebral injection of imatinib, a GSAP inhibitor, reduced Aβ levels and deposition in the 3xTg mice (18). However, despite its implication in AD pathogenesis the molecular mechanism controlling its expression is unknown.…”
Section: Discussionmentioning
confidence: 95%